If you only knew - Vail, Rachel (Vail, Rachel. Friendship ring., 1998)
Seventh-grader Zoe, who comes from a big family where she's never had anything all to herself, desperately wants CJ for a best friend, but when CJ reveals that she likes the boy Zoe likes, she must make a choice.